Thermodynamic conditions control the valences state of semimetals thus affecting the behavior of PGE in magmatic sulfide liquids. (15th March 2022) - Liang, Qing-Lin; Song, Xie-Yan; Wirth, Richard; Chen, Lie-Meng; Yu, Song-Yue; Krivolutskaya, Nadezhda A.; Dai, Zhi-Hui
Abstract: In magmatic Nickel-Copper-Platinum-group elements (Ni-Cu-PGE) sulfide deposits, PGE occur as solid solution in base metal sulfides (BMS) or occur as platinum-group minerals (PGM). In different deposits, such as the world-class deposits at Jinchuan and Noril'sk district which formed from sulfide liquids with different oxygen fugacity ( f O 2 ), the proportion of PGE forming PGMs and entering BMS as solid solution are variable and the PGMs are different in mineral species and morphology. The early-cumulated massive ores from the two deposits were analyzed using Electron Probe Microanalysis (EPMA), Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS), Scanning Electron Microscope (SEM) and Focused Iron Beam and Transmission Electron Microscope (FIB-TEM). Combined with whole-rock PGE and semimetals data, this contribution discusses the effect of thermodynamic conditions (mostly f O 2 ) and semimetals on the distribution of PGE and the mineral species and morphology of PGM in magmatic sulfide deposits. The Noril'sk massive ores commonly contain 5–12 vol% of magmatic magnetite whereas magnetite is absent in the Jinchuan massive ores, which suggests that the sulfide liquid at Noril'sk had a higher oxygen fugacity ( f O 2 ) compared to the sulfide liquid at Jinchuan. In the Jinchuan massive ores, only ∼ 39 % Ir and 37 % Rh are presented in solid solution within BMS. Meanwhile, many (Ir-Rh-Pt)AsS crystals with grain sizes of 200 nm to 2.5 μm were recognized enclosed in BMS grains and cobaltite-gersdorffite solid solution (CGSS) or rarely located at BMS grain boundaries. Microstructures of the (Ir-Rh-Pt)AsS minerals suggests that they probably crystallized from the sulfide liquid together with MSS. In contrast, more than 63 % Ir and 89 % Rh are presented in solid solution within BMS and no (Ir-Rh-Pt)AsS crystal was found in the Noril'sk massive ores. On the other hand, arsenides, stannide, antimonides, tellurides and bismuthides of Pd and/or Pt (Pt-Pd-semimetal minerals) were found in the Jinchuan and Noril'sk massive ores. This study suggests that thermodynamic conditions (especially f O 2 ) control the valence states of semimetals (especially As) affecting the behavior of PGE in sulfide liquids. A relatively low f O 2 of sulfide liquids leads to a relatively high As n- /As n+ ratio, which is atomical ratio of the anion to cation of As (n represents valence number), and results in relative more Ir-AsS, Rh-AsS and Pt-As pre-nucleation clusters. These pre-nucleation clusters were enriched in or near the migrating MSS grain boundaries and finally reaching oversaturation and nucleation of (Ir-Rh-Pt)AsS crystals occurred. In contrast, a relatively high oxygen fugacity ( f O 2 ) of sulfide liquids results in a low As n- /As n+ ratio and Ir-AsS, Rh-AsS and Pt-As pre-nucleation clusters forming a negligible amount of (Ir-Rh-Pt)AsS minerals and facilitating Ir and Rh to enter MSS crystal lattice. As for the deposits formed from sulfide liquids with a relatively low f O 2, such as the deposits at Jinchuan, Yangliuping and Sudbury, the fractional crystallization of MSS together with (Ir-Rh-Pt)AsS minerals resulted in PGE differentiation.